The impact of customer journey in restaurants on sustainable marketing practices: The moderating role of digital social media - Yassin Ibrahim Hussein; Ahmed Dheyauldeen Salahaldin (Heritage and Sustainable Development)
This study examines how the customer journey, with its various elements, influences sustainable marketing practices. It also examines the moderating effect of digital social media on this relationship. A questionnaire was used to collect data from eight restaurants located in Anbar, Iraq, which are known for their advanced services. A PLS-SEM model was used to analyse data from a sample of 379 questionnaires distributed to customers of the selected restaurants. The results indicated that customer journey elements (staff interaction (SI), merchandise assortment (MV), shop atmosphere (SA), repatriation intentions (RI), and value experienced (VE)) play a crucial role in promoting sustainable marketing practices in restaurants. Of the six indirect effect hypotheses, three were supported, namely the moderating role of digital social media between (shop atmosphere, repatriation intentions, and value experienced) and sustainable marketing. To achieve optimal levels of marketing sustainability, effectively integrating digital social media into sustainability programs requires original thinking and innovative solutions. Restaurants can improve their sustainability levels by paying closer attention to customer journey elements to predict customer behavior and meet future needs.